১/১ সুশাসন বিতর্ক / 1/11 suśāsana bitarka - নজরুল, আসিফ 1966- (ঢাকা : অনন্যা, 2009)
Articles on governance issues in Bangladesh since November 11, 2006.
In Bengali.
Keywords: Bangladesh -- Politics and government -- 1971-